PENGEMBANGAN E MODUL INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN SISWA SDN 167 PEKANBARU - FIQRIANSYAH, MUHAMMAD (Jurnal Pendidikan Teknologi Informatika dan Sains, 2024)
This research aims to implement an interactive e-module developed using Canva in an effort to improve student understanding at SDN 167 Pekanbaru through the problem-based learning (PBL) method. This interactive e-module is designed to provide materials that are interesting and easy to understand, so that it can facilitate the learning process of students more effectively. The research method used was classroom action research (PTK) with the research subject of class IV A students. Data were collected through observations, interviews, and student comprehension tests before and after the application of interactive e-modules. The results showed that the application of interactive e-modules from Canva in PBL learning significantly improved students' understanding. This is indicated by the increase in student comprehension test scores as well as positive responses from students to the use of interactive e-modules. Thus, the use of interactive e-modules from Canva can be used as an effective alternative learning media to improve the quality of learning in elementary schools.